A study on the effects of personality traits on building effective relationships - Seyed Shahab Mousavi (Management Science Letters, 2014)
This paper presents an empirical investigation to measure the effects of five big personality traits on development of effective communication among middle level managers of the first private Iranian bank, Bank Eghtesade Novin, in city of Tehran, Iran. To measure the effects of five big personality traits, the study uses a questionnaire developed by Jackson (1974) [Jackson, D. N. (1974). Personality research form manual. Research Psychologists Press.]. In addition, to measure the impacts of effective communication we use another questionnaire. All questions are designed in Likert scale and Cronbach alphas for two mentioned questionnaires were calculated as 0.92 and 0.74, respectively. The implementation of Pearson test as well as regression analysis have revealed that there were some positive and meaningful relationship between four personality traits, openness, conscientiousness, extraversion, agreeableness, and effective communication. In addition, there was a negative and meaningful relationship between neuroticism and effective communication.